On a Subclass of Meromorphic Close-to-Convex Functions - Ming-Liang Li; Lei Shi; Zhi-Gang Wang (The Scientific World Journal)
The main purpose of this paper is to introduce and investigate a certain subclass of meromorphic close-to-convex functions. Such results as coefficient inequalities, convolution property, inclusion relationship, distortion property, and radius of meromorphic convexity are derived.